The Impact of Enzyme-Replacement Therapy on Upper Airway Obstruction in Children with Mucopolysaccharidoses: Retrospective Cohort Study - Liliya A. Osipova; Ludmila M. Kuzenkova; Leyla S. Namazova-Baranova; Anait K. Gevorkyan; Tatiana V. Podkletnova; Viktor V. Altunin; Olga V. Kozhevnikova; Liya V. Toropchina; Tatiana A. Polunina; E. V. Zelenkova; Nato D. Vashakmadze (Педиатрическая фармакология, 2018)
Background. Data on the efficacy of enzyme replacement therapy (ERT) in relation to the pathology of ENT organs and respiratory performance in sleep in children with mucopolysaccharidosis (MPS) is poorly presented in the literature. Our aim was to assess the effect of ERT on the upper respiratory tract in children with MPS. Methods. According to the case histories, we studied treatment results of children with MPS type I and II who received ERT in the Research Center of Children’s Health from January 2007 to November 2016. The severity of upper airway obstruction and its change during ERT was assessed according to indices of apnea-hypopnea and desaturation (SpO2), average/minimal SpO2, duration of SpO2 episodes < 90%, and hypertrophy degree of palatine tonsils and adenoids. Results. The severity of the obstructive sleep apnea syndrome did not progress in children (n = 15) with MPS against the background of ERT with a median duration of 38 (23; 48) months: initially, the apnea-hypopnea index was 3 (1.3; 7.7), while the repeated study — 2.6 (0.9; 13.5) (p = 0.507). There was also no statistically significant change in cardiorespiratory monitoring values. Conclusion. Long-term ERT in children with MPS type I and II interferes with the progression of airway obstruction.